Nonlocal boundary-value problem for a second-order partial differential equation in an unbounded strip - Il'kiv, V. S.; Volyanska, I. I.; Symotyuk, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
The conditions of well-posedness of a nonlocal boundary-value problem are established for a second-order linear partial differential equation in an unbounded strip in the case where the real parts of the roots of its characteristic equation are different and nonzero.